2019
DOI: 10.1038/s41436-018-0308-x
|View full text |Cite|
|
Sign up to set email alerts
|

Secondary findings from clinical genomic sequencing: prevalence, patient perspectives, family history assessment, and health-care costs from a multisite study

Abstract: Purpose: Clinical sequencing emerging in healthcare may result in secondary findings (SFs). Methods: Seventy-four of 6,240 (1.2%) participants who underwent genome or exome sequencing through the Clinical Sequencing Exploratory Research (CSER) Consortium received one or more SFs from the original ACMG-recommended 56 gene-condition pair list; we assessed clinical and psychosocial actions. Results: The overall adjusted prevalence of SFs in the ACMG 56 genes across the CSER consortium was 1.7%. Initially 32% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
131
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(145 citation statements)
references
References 32 publications
12
131
2
Order By: Relevance
“…It is also possible that the family histories are incomplete and that further relevant family information could be revealed. 8 In contrast, by integrating family history assessment, our findings indicated that selecting participants according to their family history for genomic testing significantly increased the detection of carriers for cancer syndromes. Therefore, the traditional triaging of participants by family risk assessment in our study appears to be a cost-effective alternative in contrast to genome screening unselected populations to increase the detection of clinically actionable variants.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…It is also possible that the family histories are incomplete and that further relevant family information could be revealed. 8 In contrast, by integrating family history assessment, our findings indicated that selecting participants according to their family history for genomic testing significantly increased the detection of carriers for cancer syndromes. Therefore, the traditional triaging of participants by family risk assessment in our study appears to be a cost-effective alternative in contrast to genome screening unselected populations to increase the detection of clinically actionable variants.…”
Section: Discussionmentioning
confidence: 73%
“…Some recent cohort studies have suggested that family history is not a useful tool for identifying carriers of monogenic conditions, as at least half of the carriers detected in their unselected populations did not present with a corresponding increased risk family history, nor would have met eligibility criteria for genetic testing. 8,9,11 We also detected carriers of cancer syndromes that did not meet testing guidelines according to their family history (17 participants), half of which had no family history of cancer. Possible explanations include reduced penetrance or a milder phenotype of the disease-causing variant in absence of other environmental or genetic risk factors not present in these families or that the identified variant is de novo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, there are limited data available on the frequency of SF in the population. A recently published study by Hart et al (2019) reported that 74 of 6,240 (1.2%) participants who underwent genome or exome sequencing through the Clinical Sequencing Exploratory Research (CSER) Consortium received one or more SF from the original ACMG recommended 56 genes (Hart et al, 2019). Additionally, Dorschner and coworkers classified pathogenic variants of 1,000 individuals (Dorschner et al, 2013) in a defined group of actionable genes.…”
Section: Discussionmentioning
confidence: 99%